Paragonimus and Paragonimiasis in northern Peru. Process development of Paragonimus peruvianus Miyazaki Ibañez and Miranda Felis cati L. 1969 in experimentally infected domestic cat - Ibáñez H., Nicanor (1974)
The process of the development of Parogonimus peruvianus Miyazaki, Ibóñez y Miranda, 1969 in domestic cat Felis cati L. experimentally infected by means of orally given metacercarias extracted from specimens of Pseudothelphusa chilen.is Milne Edwards, 1843 from endemic areas, has been studied.